Prognostic Role of Lymphocyte-C-Reactive Protein Ratio in Colorectal Cancer: A Systematic Review and Meta Analysis - He, Xinglong; Su, Ade; Xu, Yongcheng; Ma, Diaolong; Yang, Guoyuan; Peng, Yiyun; Guo, Jin; Hu, Ming; Ma, Yuntao (Frontiers in Oncology, 2022)
Introduction The lymphocyte-C-reactive protein ratio (LCR) is a new immunoinflammatory score and prognostic marker, but the relationship between this index and the prognosis of colorectal cancer patients remains controversial.Therefore, aim of the study was to assess the relationship between LCR and prognosis for colorectal cancer patients through a systematic evaluation and meta-analysis. Methods We systematically searched PubMed, EMBASE, Web of Science, and Cochrane Library databases for randomized controlled studies and observational studies on the relationship between LCR and prognosis of colorectal cancer patients, all searched from the date of database creation to January 6, 2022.Our primary endpoints observed were overall survival (OS) and disease-free survival (DFS) of colorectal cancer patients, and secondary observables were basic characteristics of included studies, such as country, study duration, sample size, LCR threshold, and pathological characteristics of patients in each study, such as degree of differentiation, gender, tumor location, T stage, and lymphatic metastasis. Results A total of 10 case-control studies including 7068 patients were included. Meta-analysis results showed that overall survival (OS) and disease-free survival (DFS) were worse in colorectal cancer patients with lower levels of LCR (HR=0.44, 95% CI=0.38-0.52, P<0.001; HR=0.56, 95% CI=0.41-0.76, P< 0.001).Subgroup analysis based on country, study length, sample size, and LCR threshold showed that lower levels of LCR were all associated with poorer OS (P < 0.05). Regarding pathological characteristics, patients in the low LCR group were generally poorly differentiated (OR=1.79, 95% CI=1.55-2.07, P<0.001), while there was no significant relationship with gender, tumor location, T stage, and lymphatic metastasis (P>0.05). Discussion/Conclusion LCR can be used as a prognostic marker for colorectal cancer patients, and patients with lower levels of LCR may have a poor prognosis. Due to the limitation of the number and quality of the included studies, the above findings need to be validated by more high-quality studies. Systematic Review Registration https://www.crd.york.ac.uk/prospero/, identifier CRD42022296563.